Participatory Art Activities Increase Salivary Oxytocin Secretion of ASD Children - Sanae Tanaka; Aiko Komagome; Aya Iguchi-Sherry; Akiko Nagasaka; Teruko Yuhi; Haruhiro Higashida; Maki Rooksby; Mitsuru Kikuchi; Oko Arai; Kana Minami; Takahiro Tsuji; Chiharu Tsuji (Brain Sciences, 2020)
Autism spectrum disorder (ASD) occurs in 1 in 160 children worldwide. Individuals with ASD tend to be unique in the way that they comprehend themselves and others, as well as in the way that they interact and socialize, which can lead to challenges with social adaptation. There is currently no medication to improve the social deficit of children with ASD, and consequently, behavioral and complementary/alternative intervention plays an important role. In the present pilot study, we focused on the neuroendocrinological response to participatory art activities, which are known to have a positive effect on emotion, self-expression, sociability, and physical wellbeing. We collected saliva from 12 children with ASD and eight typically developed (TD) children before and after a visual art-based participatory art workshop to measure the levels of oxytocin, a neuropeptide involved in a wide range of social behaviors. We demonstrated that the rate of increase in salivary oxytocin following art activities in ASD children was significantly higher than that in TD children. In contrast, the change rate of salivary cortisol after participatory art activities was similar between the two groups. These results suggest that the beneficial effects of participatory art activities may be partially mediated by oxytocin release, and may have therapeutic potential for disorders involving social dysfunction.